Vedolizumab plus basiliximab as second-line therapy for steroid-refractory lower gastrointestinal acute graft-versus-host disease - Gao, Zicheng; Fan, Zhiping; Liu, Zhi; Ye, Xu; Zeng, Yunxin; Xuan, Li; Huang, Fen; Lin, Ren; Sun, Jing; Liu, Qifa; Xu, Na (Frontiers in Immunology, 2024)
Background Steroid-resistant (SR) lower gastrointestinal (LGI) tract graft-versus-host disease (GVHD) is the predominant cause of morbidity and mortality from GVHD after allogeneic hematopoietic stem cell transplantation (allo-HSCT). The role of vedolizumab in the treatment of SR-LGI acute GVHD (aGVHD) remains uncertain. We aimed to assess the efficacy and safety of vedolizumab combined with basiliximab as second-line therapy for SR-LGI-aGVHD. Methods This study aimed to explore the efficacy of vedolizumab combined with basiliximab for SR-LGI-aGVHD. The primary endpoint was the overall response (OR) on day 28. Secondary and safety endpoints included durable OR at day 56, overall survival (OS), chronic GVHD (cGVHD), non-relapse mortality (NRM), failure-free survival (FFS), and adverse events. Results Twenty-eight patients with SR-LGI-aGVHD were included. The median time to start of combination therapy after SR-LGI-aGVHD diagnosis was 7 (range, 4–16) days. The overall response rate (ORR) at 28 days was 75.0% (95% CI: 54.8%–88.6%), and 18 achieved a complete response (CR) (64.3%, 95% CI: 44.1%–80.7%). The durable OR at day 56 was 64.3% (95% CI: 44.1%–80.7%). The 100-day, 6-month, and 12-month OS rates for the entire cohort of patients were 60.7% (95% CI: 45.1%–81.8%), 60.7% (95% CI: 45.1%–81.8%), and 47.6% (95% CI: 31.4%–72.1%), respectively. The median failure-free survival was 276 days; (95% CI: 50–not evaluable) 12-month NRM was 42.9% (95% CI: 24.1%–60.3%). The 1-year cumulative incidence of cGVHD was 35.7%. Within 180 days after study treatments, the most common grade 3 and 4 adverse events were infections. Nine (32.1%) patients developed cytomegalovirus (CMV) reactivation complicated with bacterial infections (25.0%, CMV infection; 7.1%, CMV viremia). Epstein–Barr virus (EBV) reactivation occurred in five patients (17.9%, 95% CI: 6.8%–37.6%). Only three patients (10.7%, 95% CI: 2.8%–29.4%) in our study developed pseudomembranous colitis. Conclusions Vedolizumab plus basiliximab demonstrated efficacy in severe SR-LGI-aGVHD and was well-tolerated. Vedolizumab plus basiliximab may be considered a potential treatment option for patients with LGI-aGVHD.